Desarrollo de una herramienta digital que establezca los criterios de diseño de acumuladores de control de pozos, según la norma API 16D de 2018 (2020)
The development of a digital tool that establishes the design criteria for well control accumulators, according to API 16D of 2018, is motivated by the need to obtain design criteria of reliable accumulators, which ensure optimal devices are operating under real well-up scenarios and in turn, that equipment is under the specifications of the international standard. This research project identified the relevant variables and equations of accumulator design. The logical sequence was also performed in order to determine the density and entropy of the inert gas under the preload, load, MOP and total discharge conditions in order to determine a required capacity and optimal preload pressure.